Mechanisms of nuclear pore complex assembly – two different ways of building one molecular machine. Issue 4 (22nd November 2017) - Otsuka, Shotaro; Ellenberg, Jan
Abstract : The nuclear pore complex (NPC) mediates all macromolecular transport across the nuclear envelope. In higher eukaryotes that have an open mitosis, NPCs assemble at two points in the cell cycle: during nuclear assembly in late mitosis and during nuclear growth in interphase. How the NPC, the largest nonpolymeric protein complex in eukaryotic cells, self‐assembles inside cells remained unclear. Recent studies have started to uncover the assembly process, and evidence has been accumulating that postmitotic and interphase NPC assembly use fundamentally different mechanisms; the duration, structural intermediates, and regulation by molecular players are different and different types of membrane deformation are involved. In this Review, we summarize the current understanding of these two modes of NPC assembly and discuss the structural and regulatory steps that might drive the assembly processes. We furthermore integrate understanding of NPC assembly with the mechanisms for rapid nuclear growth in embryos and, finally, speculate on the evolutionary origin of the NPC implied by the presence of two distinct assembly mechanisms. Abstract :